Health Care, Ethics and Nursing in Bangladesh: a personal perspective - Begum, Hasna (Nursing ethics, 1998)
Health care in Bangladesh is in a sad condition, with not enough doctors and nurses available to serve its people, but, even with this limited number of health care professionals, better care would be possible if greed for money and unaccountability to the people were controlled by the Government. Conditions for members of the nursing profession are not acceptable for those who are dedicated to serving the sick. Acknowledgement of nursing’s professional dignity is almost completely absent. In addition, the salary earned is not enough to make a living. There are in existence professional associations who are struggling for the rights of the nursing community, although few concrete results have yet been seen. This article is written from the perspective of the author’s position as a member of the Board and Treasurer of the International Association of Bioethics, and her interest in feminism and bioethics, which justifies her link with oppressed nurses (because most are women) and unethical practices in the nursing profession in Bangladesh.